PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KESULITAN SISWA MEMBACA AL-QUR’AN DI SEKOLAH SMA NEGERI 1 BANGKALAN - Ahmad Royyan Ridwani; Azhar Haq; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The Qur'an is the holy book of Islam, the Qur'an was revealed to the prophet Muhammad gradually and very extraordinary to be taught to his people. In terms of the content of the Qur'an in terms of verses, the number of letters and suras, nothing has increased or decreased, this is what makes the Qur'an look very special. Every human being, especially Muslims, has different opinions regarding the importance of reading the Qur'an, some argue that reading the Qur'an should be done every day, while others think that it does not need to be read regularly but only needs to be read at a certain time. This assumption is one of the reasons why many Muslims still stammer in reading the Qur'an. reading the Qur'an, one of the factors that causes it is that not all children participate in the activities of the Al-Qur'an education park while sitting in elementary and junior high schools so that this is what causes them to have difficulty reading the Qur'an when they go to school with a background in reading the Qur'an. behind religion. Therefore, learning to read the Qur'an is very necessary to understand its contents. So the researchers raised the issue of the role of Islamic religious education teachers in overcoming the difficulties of reading the Qur'an of students at SMA NEGERI 1 Bangkalan because SMA is a compulsory standard of study in Indonesia. From the explanation of the research context above, the researcher tries to discuss a problem related to the Al-Qur'an learning process at SMA Negeri 1 Bangkalan and takes the title: